Analisis Kesalahan Mahasiswa PGMI dalam Menyelesaikan Soal Matematika Menurut Teori Kastolan - Vina Febiani Musyadad (Edumaspul: Jurnal Pendidikan, 2021)
Abstract This study aims to analyze student errors in solving problems in mathematics based on the stages of Kastolan errors. The research was conducted at the Tarbiyah Rakeyan Santang College of Sciences with the research subjects of 22 students of the Madrasah Ibtidaiyah Teacher Education study program (PGMI). The method used is descriptive qualitative. The data collection instrument was a test item consisting of 6 questions and interviews. Based on the Kastolan stage, the types of errors are divided into 3 types, namely misconceptions, calculation errors and strategy errors. The most common mistakes made are misconceptions, which account for 50% of all errors. There are 30% strategy errors made by students and 20% of all strategy errors. Factors that cause student errors in solving math problems include: 1) Lack of students in understanding the questions given so that confusion in applying the formula to solve these problems; 2) Students do not apply the requested concept; 3) Students are not careful in calculating which causes the final result to be wrong.